Nutrition Knowledge as a Driver of Adherence to the Mediterranean Diet in Italy - Aureli, Vittoria; Rossi, Laura (Frontiers in Nutrition, 2022)
An optimal population nutritional knowledge (NK), could lead to greater adherence to the Mediterranean Diet (AMD), a recognized dietary pattern capable of preventing chronic food-related diseases. The aim of the study was to evaluate the association between NK and ADM. A representative sample of 2869 Italian adults were assessed with a self-administrated questionnaire including a NK section and a AMD section based on the PREDIMED PLUS methodology. Descriptive statistics have been performed and ordinal measures of NK score and AMD were built based on quartiles of the quantitative scores. A contingency analysis was performed to check associations between variables.The average NK score was 50±13,3, corresponding to a 56,8% of correct answers. The the average value of AMD was 6.85, corresponding to 40% of the maximum score with 31.4% of the population have low AMD, 31.3% is in the lower-middle range, 24% is in the medium-high range, and only 13.3% has high AMD. The results showed that at the increasing of AMD, the percentage of respondents with low nutritional knowledge decreases, while those with high knowledge increases. This large study showed that the AMD in Italy is low and that the health dietary pattern relates to population literacy in terms of NK. Socioeconomic aspects were strong determinants of population adherence to the Mediterranean dietary pattern as well as of NK.